Some Aspects in The Organization of Cadet Training in Higher Educational Institutions - Shukurov Nuritdin Rakhimovich; Kalauov Saydulla Aymakhanovich (Research Parks Publishing LLC, 2023)
For better mastery of technical disciplines by cadets, it is necessary to strive to create pedagogical conditions for enhancing professional learning. This article discusses certain issues of organizing training for cadets of higher educational institutions in technical disciplines